2020
DOI: 10.3390/ijms21134652
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Modifies Inflammatory Mediators and Metabolomic Profiles and Contributes to the Suppression of Obesity-Associated Breast Cancer Cell Growth

Abstract: Breast cancer is the most common cancer among women. Adiposity generally accompanies immune cell infiltration and cytokine secretion, which is ideal for tumor development. Aspirin is a chemopreventive agent against several types of cancer. The aim of this study was to investigate whether aspirin inhibits the growth of 4T1 breast cancer cells by inhibiting the inflammatory response and regulating the metabolomic profile of 3T3-L1 adipocytes. 3T3-L1 adipocyte-conditioned medium (Ad-CM) was used to mimic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Another mediator, PGE 2 , is the major derivative of cyclooxygenase (COX) catalysis and has been widely discussed as a hallmark of the link between inflammation and tumor development by promoting proliferation, invasion, metastasis, and angiogenesis ( 28 ). Accordingly, non-steroidal anti-inflammatory drugs, such as aspirin, act to inhibit PGE 2 production and have been demonstrated to inhibit tumor initiation and progression ( 29 , 30 ). It has been revealed that the overexpression of COX-2 is a prominent characteristic in all clinical stages of breast cancer patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another mediator, PGE 2 , is the major derivative of cyclooxygenase (COX) catalysis and has been widely discussed as a hallmark of the link between inflammation and tumor development by promoting proliferation, invasion, metastasis, and angiogenesis ( 28 ). Accordingly, non-steroidal anti-inflammatory drugs, such as aspirin, act to inhibit PGE 2 production and have been demonstrated to inhibit tumor initiation and progression ( 29 , 30 ). It has been revealed that the overexpression of COX-2 is a prominent characteristic in all clinical stages of breast cancer patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this article, it should be mentioned that these substances reduce the actual levels of IL-6 and TNF-α, factors known for their supporting role in tumour growth and spread, as discussed above [49,50]. Moreover, ASA has a direct effect on the production of IL-6 by adipocytes, and so it has an indirect effect on cancer [51]. ASA also stimulates apoptosis in cancer cells [52].…”
Section: Non-steroid Anti-inflammatory Drugs As "Inflammaging" Therapy In Ageingmentioning
confidence: 93%
“…Lv et al demonstrated that ropivacaine alleviated high-glucose-induced brain microvascular endothelial injury through the downregulation of MMPs and the attenuation of oxidative stress [ 163 ]. In breast cancer cells, aspirin-modified metabolites were involved in suppressing lipogenesis, oxidative stress, and neoplastic formation [ 164 ]. On the other hand, Kacprzak and Pawliczak reported that aspirin induced oxidative stress in cells, a condition also supported by the inflammatory milieu [ 165 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%